PEMBERDAYAAN MASYARAKAT MELALUI POTENSI SUMBER KESEJAHTERAAN SOSIAL - Podungge, Abdul Madjid; Patilima, Zulyumna A; Safitri, Ikraeni (Universitas Gorontalo, 2024)
The purpose of implementing Community Service (PkM) activities in Monggupo Village is to increase the potential sources of social welfare. Community service activities involves preparation for activities and outreach using the MPA (Methodology Participatory Assessment) technique. The results of the assessment found that the number of NSWS needing social welfare services (NSWS) found that the highest number of PPKS needing social welfare services in Monggupo Village was WPSE (Women Prone to Social Economy)Â with a total number of 19. In addition, it was found that the most natural product in Monggupo Village was cassava which later became a practical ingredient in making modern cakes made from cassava. These practical activities can become community entrepreneurs with modern food concepts according to the times.